A Semi-Quantitative Assay to Measure Glycosaminoglycan Degradation by the Urinary Microbiota - Nguyen, Vivian H.; Khan, Fatima; Shipman, Braden M.; Neugent, Michael L.; Hulyalkar, Neha V.; Cha, Natalie Y.; Zimmern, Philippe E.; De Nisco, Nicole J. (Frontiers in Cellular and Infection Microbiology, 2022)
Glycosaminoglycans (GAGs) are linear polysaccharides and are among the primary components of mucosal surfaces in mammalian systems. The GAG layer lining the mucosal surface of the urinary tract is thought to play a critical role in urinary tract homeostasis and provide a barrier against urinary tract infection (UTI). This key component of the host-microbe interface may serve as a scaffolding site or a nutrient source for the urinary microbiota or invading pathogens, but its exact role in UTI pathogenesis is unclear. Although members of the gut microbiota have been shown to degrade GAGs, the utilization and degradation of GAGs by the urinary microbiota or uropathogens had not been investigated. In this study, we developed an in vitro plate-based assay to measure GAG degradation and utilization and used this assay to screen a library of 37 urinary bacterial isolates representing both urinary microbiota and uropathogenic species. This novel assay is more rapid, inexpensive, and quantitative compared to previously developed assays, and can measure three of the major classes of human GAGs. Our findings demonstrate that this assay captures the well-characterized ability of Streptococcus agalactiae to degrade hyaluronic acid and partially degrade chondroitin sulfate. Additionally, we present the first known report of chondroitin sulfate degradation by Proteus mirabilis, an important uropathogen and a causative agent of acute, recurrent, and catheter-associated urinary tract infections (CAUTI). In contrast, we observed that uropathogenic Escherichia coli (UPEC) and members of the urinary microbiota, including lactobacilli, were unable to degrade GAGs.